Five on a hike together - Blyton, Enid (Hodder Children's London, 2010)
"When Dick is woken by a light flashing through his window, he is puzzled. Is someone trying to send him a coded message? And when the Famous Five hear of an escaped convict in the area, they are on red alert. The police won't help, so the Five have no choice. Yet again, they'll be solving this mystery by themselves . . ."--Provided by publisher